Wet and dry troughs over Southern Africa during early summer - Barclay, Jennifer Jayne (Department of Oceanography, 2016)
The synoptic scale structure of troughs transiting southern Africa in October and November is examined. Cases are chosen on the basis of an upper trough being present over southern Africa, and a minimum horizontal and vertical temperature change. Wet and dry troughs are differentiated by the extent and amount of interior rainfall produced. Once selected, a spatial and temporal framework was used on surface, upper-level synoptic maps and radiosonde sections. Individual and composite time-height and spatial sections are analysed for anomalies of temperature, geopotentials, kinematic, vorticity and divergence fields, dewpoint, dewpoint depression, mixing ratio, dry and total static energy and, equivalent potential temperature. European Centre for Medium Range Forecast (ECMWF) maps of vertical motion are analysed and ECMWF data were exclusively used in the wet and dry case study. The essential features of wet troughs include a large amplitude upper westerly wave with a diffluent and northward displaced sub-tropical jet stream, slow movement, westward tilted trough in the vertical and a negative - positive dipole where a high is located south of the low pressure system. In comparison dry troughs are characterised by a small amplitude upper wave, rapid movement, no tilted trough in the vertical, and a stationary high-pressure system over the western interior. Radiosonde moisture variables, circulation anomalies and ECMWF fields of moisture flux give evidence in the wet cases of inflow from the north-east, in conjunction with a ridging anticyclone south of the continent. In dry cases the trajectory of flow is north-westerly and the supply of moisture is limited. In the ECMWF composite maps of vertical motion, lift is weak over the interior in dry cases consistent with a gentle slope in the divergence profile. For wet cases upward motions are intense and widespread over the interior consistent with a steep slope in the divergence profile, and compensated by descending motions over the adjacent oceans along 30° S band. Precipitation in wet events is a combination of dynamical forcing, prefrontal moisture and unstable lower troposphere. In dry events, precursor moist inflow is limited, weak instability and, a gentle slope in the divergence/convergence fields are not conducive to sustain lift.